Aplikasi mHEALTH dalam Manajemen Luka Diabetik - Adelia Pradita; Agung Waluyo; Tuti Herawati (Journal of Telenursing (JOTING), 2023)
This study aims to determine the use of mHealth in diabetic wound management. The research method uses a literature review approach through content analysis with a search method using an electronic database consisting of ProQuest, PubMed, Science Direct, Scopus, Sage, and SpringerLink with the keywords "telemedicine," "telehealth," "mobile health," "diabetic ulcer.", and "diabetic wound" published year 2018-2022. The search results obtained 612 articles, and 12 papers were reviewed after filtering. The results showed that there were four essential components in using health for diabetic wound management, namely counseling/consultation, use of wearable devices, routine foot temperature checks, and recommendations for diabetic wound care. In conclusion, mHealth positively and effectively impacts diabetic wound management. Keywords: Diabetic Wounds, Management, mHealth, Telehealth, Telemedicine